Socioeconomic Relationship And Feeding Patterns With The Nutritional Status Of Toddlers In The Working Area Of The Amonggedo Health Center, Konawe Regency - Ari Nofitasari; Heltty Heltty; Wa Ode Aisa Zoahira; Islaeli Islaeli (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Nutritional status is a measure of success in meeting children's nutritional needs as demonstrated through attainment of weight for age. The incidence of malnutrition in the Amonggedo Community Health Center, Konawe Regency is 10.86% of children under five in 2021. This research aims to determine the socio-economic relationship and feeding patterns on the nutritional status of children under five. This research is quantitative research with a Cross-Sectional Study approach. The population in this study was 276 mothers with toddlers. The sample for this research was 73 mothers of toddlers. The sampling technique used was Cluster Random Sampling. Data collection using questionnaires and 24-hour food recall forms. The data were analyzed statistically using the chi-square test. The results of the study showed that there was a relationship between the socioeconomic and nutritional status of toddlers with a p-value of 0.036 <0.05 with a phi coefficient test of 0.279, which means a moderate relationship, and there was a relationship between feeding patterns and nutritional status of toddlers with a p-value of 0.006 <0.05 with a phi coefficient test of 0.351 which means the relationship is moderate. The conclusion from the results of this research is that socio-economic and feeding patterns are related to the nutritional status of toddlers in the working area of the Amonggedo Health Center, Konawe Regency. Suggestions from the results of this research are that mothers of toddlers should provide more nutritious food and sufficient energy for their children.